19F(p,αγ)16O: Test Reaction for the Detection System PTOLEMEOS - Chronidou, C.; Spyrou, K.; Harissopulos, S.; Kossionides, E.; Paradellis, T. (HNPS Advances in Nuclear Physics, 2020)
The reaction 19F(p,αγ)16O has been studied over the energy range Ep=850-916 keV. The excitation function has been measured and the total cross section for the resonance at Ep = 872.11 keV has been deduced. By comparison of the deduced value of σR with previous ones, a test and/or a calibration of the results of simulation programs for the efficiency of our detection system can be extracted.